2018
DOI: 10.4066/biomedicalresearch.29-17-3818
|View full text |Cite
|
Sign up to set email alerts
|

Use of topical steroids on the face among university students in Saudi Arabia

Abstract: Background: Topical corticosteroids are widely used to treat dermatological problems. The aim of this study is to assess the scale of topical steroid usage on the face among the university students. Methods: An online questionnaire has been sent by e-mail to all students of King Abdulaziz University (Jeddah, Saudi Arabia). It included questions about the use of topical steroids on the face for the last 5 y. Different photos of commonly used topical steroids including combination formulas were shown and asked i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
3
3
0
Order By: Relevance
“…1). The findings agreed with the findings of Majed et al [13]. The latter study found friends or relatives recommending in about one-third cases, pharmacists (one and internet (less than ten percent) which are even higher than that found in this study [13].…”
Section: Studies Conducted In Various Countries Includingsupporting
confidence: 93%
See 4 more Smart Citations
“…1). The findings agreed with the findings of Majed et al [13]. The latter study found friends or relatives recommending in about one-third cases, pharmacists (one and internet (less than ten percent) which are even higher than that found in this study [13].…”
Section: Studies Conducted In Various Countries Includingsupporting
confidence: 93%
“…1). The findings agreed with the findings of Majed et al [13]. The latter study found friends or relatives recommending in advertisement on television allures people mainly females toward the indiscriminate use of the cream.…”
Section: Studies Conducted In Various Countries Includingsupporting
confidence: 92%
See 3 more Smart Citations